Application of Alphaviral Vectors for Immunomodulation in Cancer Therapy - Zajakina, Anna; Spunde, Karina; Lundstrom, Kenneth (Current Pharmaceutical Design, 2017)
Background: The lack of specific and efficient cancer therapies has influenced the development of novel approaches, such as immunotherapy, which from its original application of immunogenic protein delivery has developed into the use of more sophisticated recombinant gene delivery methods to achieve better safety and efficacy profiles. This approach involves viral and non-viral delivery systems. Methods: Expression vectors have been engineered for alphaviruses, including Semliki Forest virus, Sindbis virus and Venezuelan equine encephalitis virus. For immunotherapeutic applications, recombinant particles, RNA replicons and layered DNA vectors that express tumor-associated antigens (TAAs) and cytokines have been studied in animal models and in a few clinical trials. Results: Immunization studies with TAAs and cytokines have elicited strong antibody responses and vaccination has provided protection against challenges with tumor cells in mouse models. Furthermore, the combination of TAAs and cytokines, antibodies and growth factors and the co-administration of chemotherapeutics and bacteriabased adjuvants have enhanced immunogenicity. Intratumoral and systemic delivery of recombinant alphavirus particles has demonstrated significant tumor regression and prolonged survival rates in rodent tumor models. Conclusion: Alphavirus-based immunotherapy represents a rapid and efficient method for prophylactic and therapeutic applications in animal models.
Keywords: Alphaviruses